2012
DOI: 10.1089/thy.2011.0169
|View full text |Cite
|
Sign up to set email alerts
|

Three-Gene Molecular Diagnostic Model for Thyroid Cancer

Abstract: Background: The preoperative diagnosis of thyroid nodules primarily depends upon fine needle aspiration (FNA) cytology. However, up to 25% of FNA samples have associated ''suspicious or indeterminate'', but not diagnostic cytologic reports, resulting in difficulty deciding appropriate clinical management for these patients. We hypothesize that the use of molecular markers as an adjunct to FNA cytology can improve the distinction of benign from malignant nodules that have associated suspicious or indeterminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Although a high accuracy has been demonstrated by these studies, most have failed to show optimal sensitivity and specificity in the validation analysis using independent sample sets. Molecular profiling analyses usually yield a large number of potential biomarkers; however, small sets would be more viable in clinical practice, with the use of RT-qPCR or immunohistochemistry (16).…”
mentioning
confidence: 99%
“…Although a high accuracy has been demonstrated by these studies, most have failed to show optimal sensitivity and specificity in the validation analysis using independent sample sets. Molecular profiling analyses usually yield a large number of potential biomarkers; however, small sets would be more viable in clinical practice, with the use of RT-qPCR or immunohistochemistry (16).…”
mentioning
confidence: 99%
“…It has been reported that HMGA2 is overexpressed in PTC and can be used as a biomarker for distinguish- ing benign from malignant thyroid tumors. 14,15,22,25,27 The KEEG pathway analysis in this study showed that HMGA2 was enriched in the pathway of "transcriptional misregulation in cancer" .The correlation coefficient between HIT000218960 and HMGA2 was 0.999083. In addition, qRT-PCR results indicated that HIT000218960 was significantly upregulated in PTC tissues compared with noncancerous thyroid tissues, which was consistent with microarray data ( Fig.…”
Section: Identification Of Lncrna-hit000218960 Potentially Associatedmentioning
confidence: 61%
“…11,28 A 3-gene model (HMGA2, MRC2, and SFN) was used to detect malignancy in thyroid nodules, with 71% sensitivity and 84% specificity by qRT-PCR on FNA samples. 11 Using high-dimensionality genomic analysis for molecular classification of thyroid tumors, Chudova et al 28 found a 96% NPV and 84% specificity. In our study, the HMGA2 and IMP3 combination model was analyzed to determine whether this model can increase the test sensitivity and NPV for thyroid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Overexpression of HMGA2 was reported in a number of malignant tumors, including thyroid carcinomas. [5][6][7][8][9][10][11] In previous studies, we reported HMGA2 overexpression in thyroid malignances compared with benign lesions, using a relative quantitative reverse transcription-polymerase chain reaction (qRT-PCR) method. 7,8 IMP3 is a member of the insulin-like growth factor II mRNA-binding protein (IMP) family, which consists of IMP1, IMP2, and IMP3.…”
mentioning
confidence: 99%